(3GdCfhGQ GdHOQjI dcTa THg GdbOQjIs - (3GdMSf Hf eMeO Hf Ydj GdegdHj, YR GdOjf , J (B840 (3g`s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO aChdi eG JhLgJ Edjg Gdgee GdYhGdi eYQaI eG Hg jahR GdSGHb s
(3BNQgG (B:s
(3hGUdM eG CNWCJ ajg HaVdg haWfJg GSJZaQ Gddg ef Sgh s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B138s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa s
Keywords: (3GdJhMjO hGdedd hGdfMds